Anti-β-amyloid aggregation activity of enantiomeric furolactone-type lignans from Archidendron clypearia (Jack) I.C.N. Issue 4 (16th February 2020) - Wang, Yu-Xi; Lin, Bin; Zhou, Le; Yan, Zhi-Yang; Zhang, Han; Huang, Xiao-Xiao; Song, Shao-Jiang
Abstract: The phytochemical investigation on the twigs and leaves of Archidendron clypearia (Jack) I.C.N. led to the isolation of three pairs of furolactone-type lignans enantiomers, including a pair of new compounds (1 R, 5 S, 6 S )-Kachiranol (1a ) and (1 S, 5 R, 6 R )-Kachiranol (1b ) and four known compounds (2a /2b and 3a /3b ). Separation of the furolactone-type lignans enantiomeric mixtures was achieved using chiral HPLC for the first time. Their structures were determined by spectroscopic analysis and comparison between the experimental and calculated electronic circular dichroism (ECD) spectra. All optical pure compounds were evaluated for their inhibitory effects on β -amyloid aggregation by ThT assay. Among them, the inhibitory activity of the compound 1b (71.1%) was higher than the positive control (61.0%) and other compounds. In addition, molecular dynamics and molecular docking were employed to explore the binding relationship between the ligand and the receptor. Graphical Abstract: